Rancang Bangun Grease Trap Portable Ber-Auto-Drain untuk Pengelolaan Minyak Dapur Rumah Tangga - Faisal Anhar; Ariel Sulthon; Bella Adidayana; Aulia Anisa A; Braja Denta S (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Kitchen wastewater from households and small culinary businesses contains high amounts of oil and grease that can clog drains and pollute water bodies. Conventional grease traps retain oil effectively but require frequent manual cleaning, and delayed maintenance lets oil escape into the drain. This community-service activity designed, built, and introduced a multi-compartment portable grease trap equipped with an auto-drain system to residents of Perumahan Telaga Harapan, Cikarang Barat, Bekasi. The device is a 360 mm × 250 mm stainless-steel tank, 300 mm wide, with a 175 mm effective water level, four functional zones, and a 20-minute detention time; its auto-drain discharges trapped oil to an external container through a half-inch ball valve without draining the tank. Acceptance was measured using a Likert questionnaire given to 13 residents. Functional aspects scored 4.0–4.6 (good to excellent), whereas affordability and installation scored low, indicating that the device is beneficial but needs cheaper and more adaptable designs.